The value of spectrophotometric intracutaneous analysis in the noninvasive diagnosis of nonmelanoma skin cancers. (18th June 2013) - Hacioglu, S.; Saricaoglu, H.; Baskan, E. B.; Uner, S. I.; Aydogan, K.; Tunali, S.
Summary: Background. Spectrophotometric intracutaneous analysis (SIAscopy) is a recently introduced, noninvasive, rapid and practical method for monitoring pigmented lesions, which calculates the amount of collagen, melanin and haemoglobin deep in the papillary dermis. Aim. To evaluate the value of SIAscopy in the diagnosis of nonmelanoma skin cancers (NMSC). Methods. In total, 80 lesions of 76 patients were clinically evaluated by the first investigator, and the data recorded. Eight months after the clinical evaluation, all lesions were evaluated again by the same investigator, using images (SIAgraphs) obtained by the SIAscope. All SIAgraphs were also evaluated by a second investigator, and all dermatoscopic images by a third, independently of each other. All diagnoses were compared with histopathological diagnoses. Results. The clinical diagnosis was calculated to have a sensitivity of 79% and specificity of 84%. The SIAscopic diagnoses of the first and second investigators had a sensitivity of 55% and 93%, and a specificity of 88% and 53%, respectively, while the dermatoscopic diagnoses of the third investigator had a sensitivity of 86% and specificity of 80%. There was no statistical accordance between the first and second investigators according to the accuracy of SIAscopic diagnoses ( P < 0.01). The area under the curve for the receiver operator characteristic was 0.82 for clinical diagnosis, 0.73 and 0.80 for the SIAscopic evaluation of the first and the second investigators, respectively, and 0.87 for the dermatoscopic evaluation of the third investigator. Conclusions. Our findings show that dermatoscopic findings are more valuable than SIAscopic and clinical findings for the noninvasive diagnosis of NMSC. We consider that SIAscopy makes no substantial contribution towards the differential diagnosis of NMSC.